Implementation of Smart Library in Improving Services at the Gowa Regency Library and Archives Office - Nur Hijrah; Lukman Hakim; Syukri (Universitas Muhammadiyah Makassar, 2026)
The development of information technology has driven changes in various public service sectors, including libraries which are required to adapt from conventional services to digital-based services. Smart Library is a form of service innovation that utilizes information and communication technology to improve accessibility, effectiveness, and quality of library services. This research aims to analyze the implementation of Smart Library in improving the quality of services at the Gowa Regency Library and Archives Office. This study uses a qualitative method with a descriptive type. Data collection techniques are carried out through observation, interviews, and documentation with informants consisting of library staff, digital service managers, service coordinators, and library visitors. The data analysis used the Miles and Huberman model, while the implementation study used David C. Korten's theory which included aspects of the program, implementers, and target groups. The results of the study show that the implementation of Smart Library has gone well and has a positive impact on improving the quality of library services. The use of digital services such as the iGowa application, Online Public Access Catalog (OPAC), and social media is able to provide easy access to information, speed up the service process, and increase public participation in using technology-based library services. However, the implementation of the program still has limitations in the form of internet network constraints, limited supporting facilities, and differences in people's digital literacy skills. Therefore, it is necessary to strengthen technological infrastructure, increase human resource capacity, and digital literacy education so that the implementation of Smart Libraries can run more optimally.